The Journey of Indonesia Foreign Policy and Recommendations in Responding Global Terrorism and Radicalism - Dorpaima Lumbangaol (Mengeja Indonesia Publisher, 2021)
Terrorism is a significant issue in national and global security. Since the 9/11 terrorist attacks in New York, USA, the fight against terrorism has continued to this day. Resistance to terrorists has also changed the stereotype of Muslims, which affects Indonesia's reputation as the largest Muslim country in the world. The Bali I bombing attacks in 2002 by Jamaah Ansharut Daulah (JAD) terrorism group reconstructed its identity as Islam Moderate and Indonesia's foreign policy. The method used is the literature study method. Literature study is all efforts made by researchers to collect various information relevant to the topic or problem that will be studied. Through the identity, Indonesia can convince the western countries that Indonesia is worth reflecting true Islam and space to involve in the international political stage. As a pioneer of the Non-Aligned Movement and track record in the region, Indonesia trusted to be a role model for the Islamic world, especially the Middle East, that Islam and democracy are compatible. Through this, Indonesia seed as a strategic country to build international cooperation against radicalism and terrorism, which still becomes a global challenge presently.